Clinical Characteristics and Factors Associated with Disease Progression of Mild to Moderate COVID-19 Patients in a Makeshift (Fangcang) Hospital: A Retrospective Cohort Study - Liu J; Zhang JF; Ma HN; Feng K; Chen ZW; Yang LS; Mei B; Zhang JJ (Dove Medical Press, 2021)
Jia Liu,1,* Jun-Fei Zhang,2,* Han-Ning Ma,2 Ke Feng,2 Zhong-Wei Chen,2 Li-Shan Yang,2 Bin Mei,3 Jun-Jian Zhang4 1Medical Experimental Center, General Hospital of Ningxia Medical University, Yinchuan, Ningxia, 750000, People's Republic of China; 2Department of Emergency Medical, General Hospital of Ningxia Medical University, Yinchuan, Ningxia, 750000, People's Republic of China; 3Department of Social Medical Development, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People's Republic of China; 4Department of Neurology, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhong-Wei Chen; Li-Shan Yang Email 13995390007@163.com; nyfyyls@126.comObjective: Information regarding the epidemiology and clinical features of mild to moderate patients caused by COVID-19 in Fangcang Hospital is scarce. Through a retrospective cohort study, the clinical characteristics of COVID-19 patients in Dongxihu Fangcang shelter hospitals were analyzed, and the factors that affected the disease progression of COVID-19 patients were explored.Methods: The clinical characteristics of 714 patients with COVID-19 were retrospectively analyzed at Dongxihu Fangcang Hospital between February 7 and March 8, 2020. We described the clinical characteristics and distribution of discharge or transfer times for each patient. According to the disease progression of COVID-19 patients, we divided all patients into Non-Deteriorated group and Deteriorated group. Furthermore, binary logistic regression was used for a single outcome and multiple response variables.Results: We treated 789 patients with mild and moderate COVID-19, of which 714 were included in this study, which included 326 (45.66%) deteriorated patients and 388 (54.34%) non-deteriorated patients. The mean age of the study population was 48.16± 12.44 years. Of all patients, 319 (44.7%) were men and 395 (55.3%) were women. The average length of the patient's stay was 16.08± 5.13 days. The most common clinical feature on admission was fever (593 of 714, 83.05%). It is worth noting that 80 (11.20%) of the 714 patients were asymptomatic from exposure to admission. Multivariate logistic regression analysis showed that gender, age, diabetes, respiratory system disease, fever, dyspnea, and nasal congestion were risk factors associated with deterioration in cases with COVID-19 patients, and asymptomatic (OR: 0.058; 95% CI: 0.022- 0.155; P< 0.001) was the protective factor for deterioration of COVID-19 patients.Conclusion: Accompanied by chronic diseases, old age, fever, nasal congestion, and dyspnea were factors that influenced the aggravation of COVID-19 patients, and more attention and treatment should be given to these patients.Keywords: clinical characteristics, mild to moderate, makeshift (fangcang) hospital, influence factors